Persepsi Siswa SMA N3 Bandar Lampung Terhadap Pembelajaran Masa DepanMenggunakanVirtual Reality - Nova Irawati Simatupang; Leony Sanga Lamsari Purba; Elferida Sormin; Nelius Harefa; Familia Novita Simanjuntak; Sumiyati; St Fatimah Azzahra (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
Abstract Technology, which is developing very rapidly in the 21st century, has an impact on various aspects of life, one of which is the world of education. Advances in computer and smartphone-based technology are a current trend. Technological developments in the world of education, for example, include the emergence of technology-based media or learning resources such as learning media with web-based Virtual Reality (VR). Web-based Virtual Reality (VR) is a new innovation in the world of education to be able to create innovations that will have an impact on increasing students' interest in learning chemistry material. Virtual Reality is a media that combines text, animation, video, images and audio in one application. The research used wes a qualitative descriptive method by providing VR research products in class and then distributing a questionnaire regarding high school students’ perceptions of VR. The results of the research show that students’ perceptions of media using virtual reality.